Novel high glass temperature sugar-based epoxy resins: Characterization and comparison to mineral oil-based aliphatic and aromatic resins - P. Niedermann; G. Szebenyi; A. Toldy (eXPRESS Polymer Letters, 2015)
Curing and rheological behaviour, glass transition temperature, mechanical and thermal properties of two newly synthesized glucopyranoside- (GPTE) and glucofuranoside- (GFTE) based renewable epoxy resin (EP) components were investigated and compared to aromatic and aliphatic EPs. The glucose-based EPs can be successfully cured with amine and anhydride type curing agents, their gel times are suitable for processing and can be well-adopted to the needs of the common composite preparation methods. GPTE showed the highest glass transition temperature (Tg) among all investigated resins, followed by GFTE and DGEBA. Below the Tg there was no significant difference between the storage modulus values of the EP systems. The glucose-based EPs had lower tensile and bending strength, but their tensile modulus values are not significantly different from the mineral oil based EPs. The thermal stability of the synthesized GPTE and GFTE is between DGEBA and the aliphatic resins. In applications where bending stresses are dominant over the tensile ones, and outstanding Tg is required, these glucose-based resins offer a feasible renewable option.